Consequences of large impacts on Enceladus' core shape - Monteux,J; Collins,GS; Tobie,G; Choblet,G (Icarus, 2015)
The intense activity on Enceladus suggests a differentiated interior consisting of a rocky core, an internal ocean and an icy mantle. However, topography and gravity data suggests large heterogeneity in the interior, possibly including significant core topography. In the present study, we investigated the consequences of collisions with large impactors on the core shape. We performed impact simulations using the code iSALE2D considering large differentiated impactors with radius ranging between 25 and 100 km and impact velocities ranging between 0.24 and 2.4 km/s. Our simulations showed that the main controlling parameters for the post-impact shape of Enceladus’ rock core are the impactor radius and velocity and to a lesser extent the presence of an internal water ocean and the porosity and strength of the rock core. For low energy impacts, the impactors do not pass completely through the icy mantle. Subsequent sinking and spreading of the impactor rock core lead to a positive core topographic anomaly. For moderately energetic impacts, the impactors completely penetrate through the icy mantle, inducing a negative core topography surrounded by a positive anomaly of smaller amplitude. The depth and lateral extent of the excavated area is mostly determined by the impactor radius and velocity. For highly energetic impacts, the rocky core is strongly deformed, and the full body is likely to be disrupted. Explaining the long-wavelength irregular shape of Enceladus’ core by impacts would imply multiple low velocity (<2.4 km/s) collisions with deca-kilometric differentiated impactors, which is possible only after the LHB period.